The Comparison of Silver and Laser Soldering Techniques on Periodontal Tissues: A Preliminary Study - Ezgi Atik; Ceyda Kanlı Dursun; Cenk Ahmet Akcan; Hakan El; Tolga Fikret Çözüm; Semra Ciğer (Galenos Yayinevi, 2014)
Objective:The aim of this study was to compare the inflammatory effects of conventional and laser soldering methods on periodontal tissues in orthodontics.Materials and Method:Forty specimens were acquired from 10 patients whose treatment plan consisted of extraction of 4 first premolars. Before performing the extractions, a transpalatal arch (TPA) for the upper first molars and a lingual arch for the lower first molars were placed for anchorage purposes. Upper left and lower right first molar bands were soldered using the laser welding (LW) technique, and upper right and lower left first molar bands were soldered using the conventional silver soldering technique (CSS). Gingival crevicular fluid (GCF) analysis was used for determining the effects of welding procedures on periodontal tissues. All variables were analyzed by nonparametric tests.Results:Myeloperoxidase levels ranged between 2.46 and 3.56 for the CSS group and between 2.20 and 3.39 for the LW group; nitric oxide levels ranged between 4.92 and 7.13 for the CSS group and between 4.39 and 6.78 for the LW group. Both levels showed the highest level on the seventh day. Plaque index and gingival index scores ranged between 0 and 1 for all specimens. Bleeding on probing levels ranged between 45% and 75% and between 60% and 75% for the CSS group and LW group, respectively.Conclusion:There was no significant difference between laser welding and conventional soldering methods in terms of periodontal tissue response.